Emerging Materials for Interfacial Solar‐Driven Water Purification. (2nd January 2023) - Cao, Sijia; Thomas, Arne; Li, Changxia
Abstract: Solar‐driven water purification is considered as an effective and sustainable technology for water treatment using green solar energy. One major goal for practical applications is to improve the solar evaporation performance by the design of novel photothermal materials, with optimized heat localization and water transport pathways to achieve reduced energy consumption for water vaporization. Recently, some emerging materials like polymers, metal‐organic frameworks (MOFs), covalent organic frameworks (COFs) and also single molecules were employed to construct novel solar evaporation systems. In this minireview, we present an overview of the recent efforts on materials development for water purification systems. The state‐of‐the‐art applications of these emerging materials for solar‐driven water treatment, including desalination, wastewater purification, sterilization and energy production, are also summarized. Abstract : Research on solar‐driven water purification has grown rapidly over the past years and emerging materials such as polymers, MOFs and COFs have been employed in this field recently. This minireview gives an overview of the basic concepts and principles for solar evaporation systems and on the development of novel photothermal materials.